Первые товарищи: [повесть] / Лилия Чарская ; [художник А. Кузьмин] - Чарская Лидия Алексеевна (Мировая книжка, 2012)
Экземпляры: Лутохинская с/б (20210415) / Инвентарный номер: 39249 / Цена: / Авт.знак: Ч-22 / ББК: 84(2Рос=Рус)1-44